A Study on Islamic Psycho-Spiritual Therapy on Recovered Adolescent Addicts - Ismail, Nik Ahmad Hisham; Haris, Ridwan Haris; Kassim, Siti Kholijah; Awang Mat, Muhamad Zahiri (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Therapeutic intervention on drug addiction with a spirituality approach is interesting to pursue since many studies have produced various results. The focus of this study is on psycho-spiritual problems on individuals who had experienced drug addiction. The problems are loss of awareness and mind, physical and mental weakness, anti-social behaviors and problems in the school. Thus, a more in-depth study of the role of spirituality on this problem in increasing mentality, conscious mind and behaviors as a normal personality. To accomplish this, the researchers explored four individuals who had recovered from an addiction and had undergone Islamic therapeutic intervention at Inabah Centre in Tasikmalaya and Madani Health Care in Jakarta, Indonesia. The findings revealed that they gained enlightenment and consciousness, were reflective and regretful, had self-confidence and were persistent in doing good deeds after going through the recovery process. All aspects of the findings were generated into four themes, namely reflection feeling (RF), insight awareness (IA), expression attitude (EA), and brightness image (BI). Some aspects of psycho-spiritual from Islamic perspective were also explained in the discussion to make it a valuable force in preventing, treating and handling the addiction in society.